Sua nova majestade a soja : um paradidático como estratégia pedagógica para o ensino de química em Mato Grosso - Pupo, Daiana Dal (2015)
This study presents a research into preparation and evaluation of a educational material on the topic Soybean and its possibility of contributions as a pedagogical strategy to chemistry instruction in the basic education in the teachers and undergraduate students’ view. This search chose the qualitative approach as theoretical and methodological assumption through an exploratory and documental procedure. In order to identify the works about this issue, Chemistry teaching textbooks were analyzed, approved by PNLD/2012. Then, several theoretical contributions were searched, starting with characterization of teaching resources, textbooks and educational materials. After analysis of these materials, we could observe that soybean theme is a wide area to exploration of teaching learning process about chemistry concepts, and there is a lack of studies with this approach. Because of this, our educational material became a possibility of joining a content next to the students’ reality, involving the production of soy and all chemical reactions associated, with a Science, Technology and Society approach giving greater importance to the comprehensive training of the student. On such assumptions, the material was prepared and published. In order to assess the effectiveness of this material (considering the level of efficiency of technical and educational aspects to the STS (science, thecnology and society) approach and its use in the classroom), has been made available an evaluative questionnaire to members of Program for Scholarships for Beginner Teachers (PIBID). From the systematic analysis of the conclusions of the research subjects it was concluded that “The New Majesty: Soybean” sets in a valid and useful educational tool for students, it contains accessible language and deals with the contents in an attractive way, and, for the teachers who stated the usefulness of the material in the student teaching learning process.